Effect of Maternal Antibodies on Histopathogenesis of Newcastle Disease Virus in Broiler Chickens - I Made Galih Diparayoga; Nyoman Mantik Astawa; Anak Agung Ayu Mirah Adi (Udayana University, 2016)
The aims of this research were to overview the effect of maternal antibodies on the histopathological changes and viral antigen distribution of the broiler chickens challenged with ND APMV-1 virus. A total of 100 chicken were allotted into 3 treatment groups consisting of group I (titer antibodies< 23 HI Unit), group II (titer antibodies 23 – 24 HI Unit) and group III (titer antibodies> 24 HI Unit). All group I, II and III were inoculated with ND virus isolates of type viscerotropic velogenic at the dose of 1000 TCID50. The histopathological changes observed in nervous system were endotheliosis and perivascular cuffing. Immunohistochemistry staining showed that NDV infected cells were found in most organs both in inflammatory cells and in epithelial cell of many organs mainly in nervous, respiratory and digestive systems. Neurological symptoms and neural lesions were highest in group II (titer antibodies 23 – 24 HI Unit)